Weather conditions affect spring migration departure of Ruddy-headed Goose in the southern Pampas, Argentina - Pedrana, Julieta; Gorosabel, Antonella; Kazimierski, Laila Daniela; Pützd, Klemenes; Bernad, Lucía; Laneri, Karina Fabiana (Taylor and Francis, 2024)
The Ruddy-headed Goose (Chloephaga rubidiceps) has two separate populations: one sedentary, which resides in the Falkland/Malvinas Islands and one migratory that overwinters mainly in the Pampas region (Argentina) and breeds in Southern Patagonia (Argentina and Chile). The migratory population has decreased considerably to less than 800 individuals and is categorised as Endangered in Argentina and Chile. Knowing the dates at which birds leave the wintering grounds might help to predict the arrival date at stopover sites and breeding areas. We aimed to examine the effect of meteorological conditions on the decision of Ruddy-headed Geese to start spring migration and their migration strategy. We used data from six adults, equipped with satellite transmitters, over 4 years (2015–2018), giving 12 individual departure dates. Weather conditions on departure dates were compared with that during the 15 preceding days. We tested the influence of weather conditions on the response variable measured as a comparison of pre-migration dates versus departure dates. Our results showed that Ruddy-headed Geese departure from their wintering grounds is in association with high wind speed, good visibility and low percentage of cloud cover. The relationship between meteorological conditions and the species decision to start spring migration is essential information for future management plans to prevent potential human-sheldgeese conflicts to escalate along their migration route. Recommendations for the conservation of this species that include implementing mitigation measures to reduce bird collision at human infrastructure, could be applied more specifically during the periods when birds are expected to arrive in each area.